Impact of Novel Resistance Profiles in HIV-1 Reverse Transcriptase on Phenotypic Resistance to NVP - Liyan Jiao; Hanping Li; Lin Li; Daomin Zhuang; Yongjian Liu; Zuoyi Bao; Siyang Liu; Jingyun Li (AIDS Research and Treatment)
Objective. To clarify the impact of H221Y mutation on drug resistance to NVP. Methods. 646 bp HIV-1 pol gene fragments (from 592 to 1237 nucleotide) with different NNRTIs mutation profiles from AIDS patients receiving antiretroviral therapy containing NVP regimens were introduced into pNL4-3 backbone plasmid. H221Y and (or) Y181C mutations were reverted to wild type amino acids by site-directed mutagenesis, then strains containing various mutation patterns were packaged. Phenotypic drug resistance was analyzed on TZM-bl cells. Results. 12 strains containing different drug-resistant mutation profiles were constructed, including the K101Q series (K101Q/Y181C/H221Y, K101Q/Y181C, K101Q/H221Y, and K101Q), the V179D series (V179D/Y181C/H221Y, V179D/Y181C, V179D/H221Y, and V179D), and the K103N series (K103N/Y181C/H221Y, K103N/Y181C, K103N/H221Y, K103N). For strains containing the mutation profiles (K101Q/Y181C, K101Q, V179D/Y181C, V179D, K103N/Y181C, and K103N), the presence of H221Y reduced NVP susceptibility by 2.1±0.5 to 3.6±0.5 fold. To the mutation profiles K101Q/H221Y, K101Q, V179D/H221Y, V179D, K103N/H221Y, and K103N, the presence of Y181C reduced NVP susceptibility by 41.9±8.4 to 1297.0±289.1 fold. For the strains containing K101Q, V179D, and K103N, the presence of Y181C/H221Y combination decreased NVP susceptibility by 100.6±32.5 to 3444.6±834.5 fold. Conclusion. On the bases of various NNRTIs mutation profiles, Y181C remarkably improved the IC50 to NVP, although H221Ymutation alone just increases 2.1 ∼ 3.6-fold resistance to NVP, the mutation could improve 100.6 ∼ 3444.6-fold resistance to NVP when it copresent with Y181C, the phenotypic drug resistance fold was improved extremely. For strains containing the mutation profiles (K101Q/Y181C, K101Q, V179D/Y181C, V179D, K103N/Y181C, and K103N), the presence of H221Y reduced NVP susceptibility by 2.1±0.5 to 3.6±0.5 fold.